Scapular metastasis of hepatocellular carcinoma presenting as acute bleeding and hematoma: A case report of safe and effective treatment. Issue 46 (November 2017) - Kim, Ki-Hyun; Oh, Hyung-Hoon; Son, Dong-Jun; Hong, Ji-Yoon; Jeong, Young-Hoon; Jung, Jin-Seong; Yu, Hyeong-Min; Myung, Dae-Seong; Cho, Sung-Bum; Lee, Wan-Sik; Kim, Jin-Woong; Joo, Young-Eun
Abstract: Rationale: The occurrence of bleeding and hematoma from bone metastasis of hepatocellular carcinoma (HCC) is extremely rare. Patient concerns: We present a case of scapular metastasis of HCC in a 69-year-old man who presented with acute bleeding and hematoma. Diagnoses: Chest computed tomography showed a large hematoma within the right pectoral muscle of the right upper chest and an exophytic metastatic mass in the right scapula with bony destruction, which caused the intramuscular hematoma. The final diagnosis was scapular metastasis of HCC presenting as acute bleeding and hematoma. Interventions: Selective right subclavian angiography showed a hypervascular metastatic lesion in the right scapula. Subsequently, embolization of the tumoral feeding artery using a microcoil was performed and tumoral bleeding was stopped. Outcomes: The patient was discharged on hospital day 14 without any complications. Lessons: Despite being extremely rare, the possibility of bleeding from bone metastasis of HCC needs to be considered. Transcatheter arterial embolization may be an effective means to treat bleeding from bone metastasis of HCC.